2023
DOI: 10.1136/bmjopen-2023-075311
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum triglyceride to high-density lipoprotein cholesterol ratio and sarcopenia among elderly patients with diabetes: a secondary data analysis of the China Health and Retirement Longitudinal Study

Yinghe Lin,
Shanshan Zhong,
Zhihua Sun

Abstract: ObjectivePrevious studies investigating the association between the serum triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio and the occurrence of sarcopenia in different populations have yielded inconsistent results. This study aimed to investigate the potential association between TG/HDL-C ratio and sarcopenia among elderly Chinese patients with diabetes.DesignA secondary data analysis.SettingThis was a secondary analysis of data from the China Health and Retirement Longitudinal Study.Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
2
0
1
Order By: Relevance
“…Wang et al (14) found a negative association between sarcopenia and TG/HDL-C ratio in community-dwelling adults in China. In addition, Lin et al (31) studied older patients with DM in China and found that there was a negative association between TG/HDL-C ratio and sarcopenia, indicating that a higher TG/HDL-C ratio was associated with better muscle status. Differently, in the current study, we found that the TG/HDL-C ratio was negatively associated with the relative grip strength in adults aged ≥60 years old, which indicated that the TG/HDL-C ratio may be suggested to be controlled at an appropriate level in clinical practice and may benefit to prevent and control sarcopenia in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (14) found a negative association between sarcopenia and TG/HDL-C ratio in community-dwelling adults in China. In addition, Lin et al (31) studied older patients with DM in China and found that there was a negative association between TG/HDL-C ratio and sarcopenia, indicating that a higher TG/HDL-C ratio was associated with better muscle status. Differently, in the current study, we found that the TG/HDL-C ratio was negatively associated with the relative grip strength in adults aged ≥60 years old, which indicated that the TG/HDL-C ratio may be suggested to be controlled at an appropriate level in clinical practice and may benefit to prevent and control sarcopenia in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…самый высокий шанс иметь саркопению был в группе ТГ/ЛПВП ≥ 3,9 (ОШ = 2,10, p = 0,001). В Китае при обследовании 752 пациентов старше 60 лет с диабетом получены противоположные результаты: высокое соотношение ТГ/ЛПВП > 4,71 в сравнении с низким ТГ/ЛПВП < 1,41 у мужчин и ТГ/ЛПВП > 5,61 в сравнении с ТГ/ЛПВП < 2,07 у женщин коррелировало с большей мышечной массой у обоих полов (p < 0,001 для мужчин, p = 0,003 для женщин) [14]. Риск саркопении был меньше в группах с высоким соотношением ТГ/ЛПВП как у мужчин, так и у женщин (p ≤ 0,001).…”
Section: связь дислипидемии со саркопениейunclassified
“…Several studies have reported on sarcopenia and abnormalities of lipid metabolism [ 15 ]. Multiple cross-sectional investigations have revealed an inverse relationship between the triglyceride/HDL-C ratio and relative grip strength, indirectly showing that lipid metabolism monitoring-related indicators reflect muscle loss [ 16 18 ]. When investigating lipoprotein subfraction levels in individuals with sarcopenia, a significantly elevated level of non-HDL-C was found, indicating a strong relationship between sarcopenia and abnormalities in lipid metabolism [ 19 ].…”
Section: Introductionmentioning
confidence: 99%